Nag Hammadi à 70 ans, qu'avons-nous appris? = Nag Hammadi at 70, what have we learned? : (Colloque international, Québec, Université Laval, 29-31 mai 2015) - Crégheur, Éric; Painchaud, Louis; Rasimus, Tuomas (Bibliothèque copte de Nag Hammadi. Section "Etudes", 2019)
In 1945, a collection of thirteen papyrus codices containing some fifty previously unknown Christian texts was discovered in Upper Egypt near the modern village of Nag Hammadi. These fourth-century Coptic texts, originally written in Greek, have allowed us to see the great diversity that characterized early Christianity during the first centuries of the common era. Now, seventy years later, it seemed helpful to look back and evaluate what we have learned from the Nag Hammadi texts in the framework of an international colloquium. The objective was to observe progress and changes in scholarship and to consider new avenues for research. The colloquium gathered some thirty international scholars, whose contributions take stock of previous research, recent trends and advances in scholarship. These include a critique of received concepts (such as "Gnosticism" and "Docetism"), contribution of Nag Hammadi texts to our understanding of Middle- and Neoplatonism, archaeology of Egyptian monasticism, and reception of these texts in fourth-century Egypt as well as in contemporary Western culture